2016
DOI: 10.1002/jmv.24468
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis E virus infection among dogs in several developed cities in the Guangdong province of China

Abstract: Hepatitis E virus (HEV), as a zoonotic disease virus, was seldom studied in dogs especially in stray dogs. As previously reported, dog might be an accidental host of HEV for human beings and some risk factors might play an important role in HEV transmission. Thus, we designed this study to evaluate the seroprevalence of HEV infection among dogs in several cities in Guangdong province of China. This surveillance may help us understand risk factors including location, gender, live type, and diet habit for HEV tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
7
2
Order By: Relevance
“…Overall, our results indicate exposure to HEV in the pet species analysed and a widespread distribution in cat and dog populations in the study area. Ingestion of contaminated food is considered to be one of the main transmission routes of HEV in pigs and humans (Kamar et al., 2017; Meng, 2010), and probably also in cats and dogs (Liu et al., 2009; Peralta et al., 2009; Wang et al., 2016). Indeed, feeding on kitchen waste and/or animal offal has been identified as a risk factor associated with HEV seropositivity in both cats and dogs (Liang et al., 2014; Wang et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our results indicate exposure to HEV in the pet species analysed and a widespread distribution in cat and dog populations in the study area. Ingestion of contaminated food is considered to be one of the main transmission routes of HEV in pigs and humans (Kamar et al., 2017; Meng, 2010), and probably also in cats and dogs (Liu et al., 2009; Peralta et al., 2009; Wang et al., 2016). Indeed, feeding on kitchen waste and/or animal offal has been identified as a risk factor associated with HEV seropositivity in both cats and dogs (Liang et al., 2014; Wang et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Ingestion of contaminated food is considered to be one of the main transmission routes of HEV in pigs and humans (Kamar et al., 2017; Meng, 2010), and probably also in cats and dogs (Liu et al., 2009; Peralta et al., 2009; Wang et al., 2016). Indeed, feeding on kitchen waste and/or animal offal has been identified as a risk factor associated with HEV seropositivity in both cats and dogs (Liang et al., 2014; Wang et al., 2016). Nevertheless, since cats and dogs can directly or indirectly come into contact with other susceptible domestic and wild sympatric species, such as rabbits ( Oryctolagus cuniculus ), rats ( Rattus spp.)…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the rates of HEV infection in dogs are diverse in different areas, such as in Beijing, Shanghai, Guangzhou, Shenzhen and Macau. Dog HEV infection rate in 2012–2013 was 21.12% (Wang et al., ). In 2016, the dog HEV infection rate in Guangdong was 19% (Liang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, the infection of HEV among the stray dogs was relatively serious. According to the epidemiological characteristics of HE, HEV infection was closely related to the dog breeds and the daily living environment (Li, Shen, Ai, Guo, & Geng, 2014 (Wang et al, 2016). In 2016, the dog HEV infection rate in Guangdong was 19% (Liang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs are readily exposed to contaminants and may spread HEV through soil, food, and feces. Recent studies have shown a high prevalence of anti-HEV antibodies in dogs (pet or stray) and humans exposed to dogs, so dogs play an important role as an HEV reservoir and in HEV transmission (Wang et al, 2016;Zeng et al, 2017). Vegetables contaminated with feces may cause HEV infection when eaten undercooked or raw (Terio et al, 2017).…”
Section: Discussionmentioning
confidence: 99%